Barthes et Bachelard à la recherche du repos actif - Corbier, Christophe (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
I’ll start by discussing Barthes’ last lectures, in which he summoned not the author of L’eau et les rêves, but the philosopher of La Dialectique de la Durée, to define a method of reading based on the perception of intensities (particularly in the experience of the “moment of truth”), and which relies on listening. We will show how rhythm and intensity are articulated in this method, which is based on the notion of coincidence, and how Barthes’ late theory proceeds in part from Bachelard’s analyses set out in La Dialectique de la Durée. From here, we come to the book that revealed Barthes to Bachelard, Michelet par lui-même, in which rhythm and intensity are already linked in the so-called “thematic” method of reading. Like Bachelard, Barthes conceived of text as early as the 1950s as a spatialized polyphony governed by sonic and rhythmic phenomena. Barthes’ thematic reading, and the relationship between Barthes and Bachelard at that time, will lead us to the “formal imagination” that Bachelard evoked in the 1930s, and which already linked rhythm and intensity in La Dialectique de la Durée, a book that also features the musicologist Maurice Emmanuel, whose works Barthes had also read and studied in the late 1930s.